Comparison of Fishing Line for Repair of the Cruciate Deficient Stifle - Sicard, Gretchen K.; Meinen, J.; Phillips, T.; Manley, P. A. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
Numerous types of suture material have been used for extra-articular cranial cruciate ligament stabilization. Although monofilament nylon leader line is considered by some to be the most appropriate material for this procedure, monofilament nylon fishing line is a popular alternative (8, 13). The purpose of this study was to evaluate four brands of nylon fishing line in order to determine the superiority of the material as well as the sterilization method of choice. The four brands of monofilament fishing line tested were 36 kilogram test “Ande”, “Berkley”, “Hi-Seas”, and “Maxima”.“Ande” and “Maxima” proved superior in strength prior to sterilization. When the materials were sterilized by ethylene oxide, minimal elongation was observed. However, there was a significant decrease in strength for three of the four materials (“Ande”, “Hi-Seas”, and “Maxima”) when compared to unsterilized or to steam sterilized samples. Steam sterilization resulted in significant elongation of all materials tested and had a variable effect on strength (either greater, equal, or less than no sterilization). Considering all materials, “Ande” was the nylon material of choice when ethylene oxide was used for sterilization, and “Ande” or “Maxima” were the nylon materials of choice when steam sterilization was used.The strength and elongation of four brands of thirty-six-kilogram test monofilament nylon fishing line were tested using a materials testing machine without sterilization and following either steam or ethylene oxide sterilization. “Ande” was the nylon material of choice when ethylene oxide was used for sterilization and “Ande” or “Maxima” were the nylon materials of choice when steam sterilization was used.
Keywords: Cranial cruciate ligament; monofilament nylon; sterilization; material properties